Geographies of knowledge and power - Meusburger, Peter; Gregory, Derek; Kaeding-Suarsana, Laura (Knowledge and space, 2015)
Interest in relations between knowledge, power, and space has a long tradition in a range of disciplines, but it was reinvigorated in the last two decades through critical engagement with Foucault and Gramsci. This volume focuses on relations between knowledge and power. It shows why space is fundamental in any exercise of power and explains which roles various types of knowledge play in the acquisition, support, and legitimization of power. Topics include the control and manipulation of knowledge through centers of power in historical contexts, the geopolitics of knowledge about world politics, media control in twentieth century, cartography in modern war, the power of words, the changing face of Islamic authority, and the role of Millennialism in the United States. This book offers insights from disciplines such as geography, anthropology, scientific theology, Assyriology, and communication science
Keywords: Wissen; Geopolitik; Räumliche Identität; Massenmedien; Geografie; Macht